Dissimilarities of gynaecological and sexological care in handicapped patients after menopause: medical and ethical aspects - Jarząbek, Grażyna; Radomski, Dariusz (Menopause Review/Przegląd Menopauzalny, 2011)
Disability is a significant risk factor decreasing the quality of women’s psychosexual life after menopause. Handicapped persons have full rights to participate in social life and are entitled to be provided with all the benefits of the healthcare system, including gynaecological and sexological prophylactic and therapeutic procedures. Mental or physical disability is an important factor influencing the ability of keeping proper standards in gynaecology. Knowledge about influence of disability on female sexuality and reproductive ability is still poor. This problem is connected with medical and ethical aspects, too.